Intercomparisons for integrating the radon-thoron detector of NIRP, China with NIRS, Japan - Wu, Y.; Cui, H.; Zhang, Q.; Shang, B. (Radiation protection dosimetry, 2015)
Intercomparisons play an important role in maintaining a reasonable and accurate standard of measurement and quality. Integrating the radon-thoron detector of the National Institute for Radiological Protection (NIRP), China has continuously been a subject of four rounds of international intercomparisons organised by the National Institute of Radiological Sciences (NIRS), Japan during 2007-12. The intercomparisons were held at NIRS. The exercises included different exposures for both radon and thoron. The results of the intercomparison for the detectors of NIRP for both radon and thoron exposures were in the range of ±20% from the reference value and were categorised as 'Category I' in the intercomparison carried out in 2011. The radon and thoron results of the LD-P detector in four rounds of intercomparison exercises were summarised, and uncertainties of all the radon and thoron results of NIRP were within the acceptable range of 30% in environment. Radon and thoron measurement results between NIRP and NIRS were basically in agreement.